Diplomasi Vaksin Covid-19 Jepang di Vietnam - Rizkiyanti, Amanda Femalia; Rosyida, Hamdan Nafiatur (Andalas Institute of International Studies UNAND, 2023)
Japan conducted its COVID-19 vaccine diplomacy through bilateral channels and independently, without relying on the COVAX Facility. Vietnam was the first country to receive vaccine assistance from Japan and received the largest dosage compared to other Southeast Asian nations. This was driven by Japan's desire to ensure the resilience of its supply chain in Vietnam, strengthen future political and economic ties, facilitate post-COVID-19 economic recovery, and solidify its image as a humanitarian aid donor. This study aims to describe the implementation of Japan's COVID-19 vaccine diplomacy in Vietnam. A qualitative research method with a descriptive approach was employed. The analysis revealed that Japan has successfully implemented vaccine diplomacy through bilateral and multilateral cooperation. As a result of this vaccine diplomacy, Japan has gained both emotional and material benefits. The emotional benefit lies in the increased trust of Vietnam in Japan, while the material benefits include Vietnam accepting Japanese companies relocated from China, promoting Japanese tourism in Vietnam, and enhancing trade relations between the two countries to aid Japan's post-COVID-19 economic revitalization.